Die lage der Fischbestände in Nordostatlantik, Nord- und Ostsee. Einschätzungen des Internationalen Rates für Meeresforschung im Frühjahr 2000 - Hammer, Cornelius; Gröhsler, Tomas; Zimmermann, Christopher (2000)
The spring session of ACFM gave advice for a number of stocks in the North Atlantic, North Sea and Baltic. The present assessment of the situation is given here for stocks of higher importance for the German fishery. These are: Blue Whiting: the stock is still relatively high, this, however, will not last very long, due to too intense fishing. Cod in Kattegat: stock is outside safe biological limits. No immediate recovery in sight. Cod in 22–24 (Baltic): stock is inside save biological limits. F, however, is above the recommendation of the IBSFC. Greenland Halibut: state of the stock not quite clear. The present fishing intensity seems to be sustainable. Herring (Atlanto- scandian, Norwegian spring spawner): stock is within safe biological limits, weak recruitment of the recent years will lead to a reduction of biomass. Herring: for Baltic spring spawner in 22–24 and IIIa still no increasing tendency detectable. North Sea Herring: further increasing tendency, with 900 000 t over B lim, good recruitment. Herring in VIa: stable. Redfish: generally decreasing tendency observed, a reduction of the fishery is recommended. Signs of recovery, however, visible for some units